Odpowiedzi

2009-10-27T21:26:57+01:00
Najpierw mnożymy 1,8 * 4/3=2,4
(3,6 - 2,4):0,4
Teraz odejmujemy 3,6-2,4=1,2
1,2:0,4
Teraz dzielimy
1,2:0,4 = 3
2009-10-27T21:30:09+01:00
(3,6 - 108 * 1 1/3) : 0,4 = (3 6/10 - 1 8/10 * 4/3) :4/10 = (36/10 - 18/10 * 4/3) :4/10 = (36/10 - 12/5) : 4/10 = (18/5 - 12/5) : 4/10 = 4/5 : 4/10 = 4/5 * 10/4 = 2
2009-10-27T21:57:36+01:00
Zaraz ci napisze odpowiedz


( 3,6 - 1,8 ( razy) 1 1/3) : 0,4 =
(3,6 -1 i 8\10 razy 1 i 1\3):0,4
(3,6-12\5);0,4=
(3,6 - 2,4):o,4=
1,2:o,4=
1 i 2\10 : 4\10= 11\2 = 5 i 1\2